The Westpalaearctic Lasius paralienus complex (Hymenoptera: Formicidae) contains three species - Seifert, Bernhard; Galkowski, Christophe (Zootaxa, 2016)
Application of Numeric Morphology-Based Alpha-Taxonomy (NUMOBAT) demonstrated the existence of three cryptic species within the Westpalaearctic Lasius paralienus species complex: L. paralienus Seifert, 1992, having a wider European distribution north to Sweden, L. casevitzi sp. nov., an endemic of Corsica, and Lasius bombycina sp. nov. from southeast Central Europe, the Balkans and Asia Minor. Hierarchical NC-Ward clustering and non-hierarchical NC-k-means clustering of 16 morphological characters resulted in 98.7% identical classifications within 76 examined nest samples of the three species. The classification error in 180 worker individuals was 0% in a linear discriminant analysis (LDA) and 1.3% in a LOOCV-LDA. Differential characters to other species groups and an identification key of the six European members of the Lasius alienus Förster species group are provided.